2021
DOI: 10.1371/journal.pone.0259723
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of induction and associated factors among induced labours in public Hospitals of Harari Regional State, Eastern Ethiopia: A two years’ retrospective analysis

Abstract: Background Induction of labor (IOL) is an essential intervention to reduce adverse maternal and neonatal outcomes. It is also improved pregnancy outcomes, especially in resource-limited countries, where maternal and perinatal mortality is unacceptably high. However, there is a scarcity of evidence regarding the outcome of induction of labor and its predictors in low-income countries like Sub-Saharan Africa. Therefore, this study was aimed at assessing the outcome of induction of labor and associated factors am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…The overall success rate for induction of labour in this study was 71.2% which was similar to 67.6% reported by Oshodi et al and 65% reported by Yimer et al, but lower than rate of 82.2% reported by Oyebode et al [ 5 , 19 20 ] Multiparous women were found to have higher chances of successful vaginal delivery with mean success rate of 91.7% than nulliparous women with rate of 58.4% which was in keeping with the findings of Oyebode et al where nulliparous women had highest rate of operative delivery [ 3 ] . With respect to indications, those induced on account of hypertensive diseases had the highest success rate (100%) followed by those who had IUFD (88.9%).…”
Section: Discussionsupporting
confidence: 85%
“…The overall success rate for induction of labour in this study was 71.2% which was similar to 67.6% reported by Oshodi et al and 65% reported by Yimer et al, but lower than rate of 82.2% reported by Oyebode et al [ 5 , 19 20 ] Multiparous women were found to have higher chances of successful vaginal delivery with mean success rate of 91.7% than nulliparous women with rate of 58.4% which was in keeping with the findings of Oyebode et al where nulliparous women had highest rate of operative delivery [ 3 ] . With respect to indications, those induced on account of hypertensive diseases had the highest success rate (100%) followed by those who had IUFD (88.9%).…”
Section: Discussionsupporting
confidence: 85%
“…This finding agrees with the study findings done in Romania [ 27 ] and Ethiopia [ 37 , 42 ]. This can be explained by labor induction causing strong uterine contractions that alter the fetal heartbeat pattern, resulting in non-reassuring fetal heartbeat pattern, which may necessitate an episiotomy to shorten the second stage of labor and save the life of the baby [ 43 ]. Appropriate use of the induction protocol and close maternal and fetal monitoring are advised during labor and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Induksi persalinan hanya diindikasikan saat risiko meneruskan kehamilan untuk ibu dan bayi lebih besar dibandingkan risiko terminasi kehamilan dengan pemberian induksi. (Beshir et al, 2021) Selama 20 tahun terakhir, induksi persalinan di negara berpendapatan menengah dan tinggu terus meningkat. (Swift et al, 2022) Pemberian oksitosin intravena merupakan metode induksi persalinan yang paling sering digunakan pada kehamilan dengan kemungkinan bayi lahir hidup tinggi dan dapat dilahirkan secara per vaginam.…”
Section: Hasil Dan Diskusiunclassified